Factors associated with psychological distress among members of HIV discordant couples in western Kenya: the role of adverse childhood experiences - Ken Ondenge; George Khalil; Isdorah Odero; Derek C Ford; William W Thompson; Eucabeth Awuonda; Tereza Omoro; Deborah A Gust (Inishmore Laser Scientific Publishing Ltd, 2018)
# Background The relationship between measures of psychological distress and factors such as adverse childhood experiences (ACE) and HIV infection have not been well studied among members of HIV discordant couples living in Kenya. # Methods A structured questionnaire, which included the non-specific psychological distress Kessler 6 (NPD K6) scale, was administered to members of HIV discordant couples using a computer-assisted personal interview in two Kenyan communities. # Results Among the 202 participants who completed the survey (52% women and 48% men), the median NPD K6 score was equal for men and women (median=4; maximum=24). Participants did not report high levels of distress. For women, factors associated with a higher or more distressed NPD K6 score were a higher ACE score, religious affiliation, and perception of not being treated with respect by family members and partners. For men, factors associated with a higher NPD K6 score were HIV-positive status and higher ACE score. # Conclusions It is important to assess NPD and ACE in members of discordant couples, and if needed, assist them in identifying psychological counselling and support activities. By being better equipped to deal with the stressors associated with not only HIV, but also the discrimination and stigma associated with the disease, members of discordant couples may be more inclined to consider the importance of treatment and prevention.